Innovation and Organizational Culture in South American Companies in the Last Decade - Villanueva Peve, Tamara Geraldine (2024)
Purpose: The current analysis aimed to review the state-of-the-art about innovation and organizational culture in enterprises placed or working in South America. Theoretical Framework: Innovation and organizational culture are critical concepts in management studies nowadays. In South America, in recent years, companies have had the trend to disrupt static and hierarchized organizations by allowing employees to participate actively in the organization's objectives. Moreover, flexible companies do not mean that hierarchies do not exist. Instead, it means that companies are eager to listen and accept the different points of view of the employees. Moreover, innovative companies seem to adapt rapidly to both beneficial and adverse environments. However, some firms resist changes and get revenues, but the evidence suggests that they put their sustainability in the long term. Design/Methodology/Approach: In consequence, the methodological approach was the employment of the PRISM method to depurate the initial bibliographic resources from EBSCO and RENATI. EBSCO was used to analyze papers, and RENATI to review theses. Initially, there were 78 articles and 271 theses to be examined. After the PRISM depuration, it was analyzed 35 papers and theses from the period lasting from 2012 to 2021. Findings: The results showed that flexible companies were more adaptative than rigid ones. Moreover, the literature suggested that flexible companies have more chances to be sustainable in the long term than other firms. Therefore, it is possible to state that innovation policies had a higher impact in flexible organizations than in rigid ones. Originality/Value: The value of the study relies on the systematic review of the current literature of innovation and organizational culture in South America which is the nearest international environment for Peruvian companies.